2009
DOI: 10.1101/gad.1862709
|View full text |Cite
|
Sign up to set email alerts
|

Fusion of nearby inverted repeats by a replication-based mechanism leads to formation of dicentric and acentric chromosomes that cause genome instability in budding yeast

Abstract: Large-scale changes (gross chromosomal rearrangements [GCRs]) are common in genomes, and are often associated with pathological disorders. We report here that a specific pair of nearby inverted repeats in budding yeast fuse to form a dicentric chromosome intermediate, which then rearranges to form a translocation and other GCRs. We next show that fusion of nearby inverted repeats is general; we found that many nearby inverted repeats that are present in the yeast genome also fuse, as does a pair of synthetical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
136
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(141 citation statements)
references
References 76 publications
4
136
1
Order By: Relevance
“…We hypothesize that some sequence on this minichromosome might have a centromere-like activity, or that the segregation of the minichromosome is coupled to the segregation of other chromosomes (35). Paek et al (36) previously used PCR to demonstrate acentric fragments in yeast generated by template switching during DNA replication, although the stability of these fragments could not be quantitated.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesize that some sequence on this minichromosome might have a centromere-like activity, or that the segregation of the minichromosome is coupled to the segregation of other chromosomes (35). Paek et al (36) previously used PCR to demonstrate acentric fragments in yeast generated by template switching during DNA replication, although the stability of these fragments could not be quantitated.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, stalled forks have recently been shown to produce DSB-independent fusions of nearby inverted-repeats, which lead to the formation of palindromic chromosomes (Mizuno et al 2009;Paek et al 2009). The mechanisms by which these fusions take place remain a subject of debate, and three distinct possibilities have been proposed: faulty template switching, tandem inversion duplications, and replication U-turns (Mizuno et al 2009(Mizuno et al , 2013Paek et al 2009;Kugelberg et al 2010;Seier et al 2012).…”
mentioning
confidence: 99%
“…Since nearby inverted repeats separated by a few kilobases of DNA are unlikely to form cruciform structures as do palindromes, it is most probable that the mechanisms leading to formation of dicentric and acentric chromosomes in these situations are also different. The recent studies by Paek et al (2009) and Mizuno et al (2009) characterized the factors influencing the formation of acentric and dicentric chromosome intermediates at nearby inverted repeats or palindromic loci in budding and fission yeast, respectively.…”
Section: Inverted Repeats Palindromes and Dicentric Chromosome Formmentioning
confidence: 99%
“…In the December 15, 2009, issue of Genes & Development, Paek et al (2009) found that, in budding yeast, naturally occurring or synthetic inverted repeats separated by ;1.3-5.5 kb of DNA and having as few as ;20 base pairs (bp) of homology can fuse to form acentric or dicentric chromosomes (Paek et al 2009). This nearby inverted repeat fusion phenomenon has been reported previously in bacteria and in fission yeast (Bi and Liu 1996;Albrecht et al 2000).…”
Section: Inverted Repeats Palindromes and Dicentric Chromosome Formmentioning
confidence: 99%
See 1 more Smart Citation